ANALYSIS OF THE EFFECT OF HIGH FREQUENCY TRADING ON THE STABILITY OF THE INDONESIAN STOCK EXCHANGE: A CASE STUDY OF THE IHSG TRADING HALT IN JANUARY 2026 - Eruandi Dorasi Samosir; Irsad Lubis (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The composite stock price index (IHSG) is used as a benchmark for investment, monitoring the fluctuations in stock prices. Generally, the Jakarta Composite Index (JCI) serves as a benchmark for capital market activity, serving as an indicator for assessing market movements. The JCI is an index on the Indonesia Stock Exchange that is highly regarded by investors when considering investments. This is because the JCI is the primary indicator of the performance of both the common and preferred stock exchanges. The JCI calculation component combines all types of stocks listed on the IDX, with the JCI having the highest value compared to other indices in Indonesia. JCI movements can be used as a consideration when investors make decisions about whether to buy, hold, or sell their shares. Some argue that increased liquidity and market efficiency can also contribute to lower trading costs for small investors. The primary cost for mutual funds comes from the spread between the buy and sell prices. This cost can be reduced by HFT activity, which narrows and reduces the final price of a security. HFT traders are able to break these large transactions into many smaller ones to mitigate the impact of large buy or sell orders.